Design, synthesis and evaluation of γ-turn mimetics as LSD1-selective inhibitors. Issue 3 (1st February 2018) - Ota, Yosuke; Miyamura, Shin; Araki, Misaho; Itoh, Yukihiro; Yasuda, Shusuke; Masuda, Mitsuharu; Taniguchi, Tomoyuki; Sowa, Yoshihiro; Sakai, Toshiyuki; Itami, Kenichiro; Yamaguchi, Junichiro; Suzuki, Takayoshi
Graphical abstract: Abstract: Lysine-specific demethylase 1 (LSD1) is an attractive molecular target for cancer therapy. We have previously reported potent LSD1-selective inhibitors (i.e., NCD18, NCD38, and their analogs) consisting of trans -2-phenylcyclopropylamine (PCPA) or trans -2-arylcyclopropylamine (ACPA) and a lysine moiety that could form a γ-turn structure in the active site of LSD1. Herein we report the design, synthesis and evaluation of γ-turn mimetic compounds for further improvement of LSD1 inhibitory activity and anticancer activity. Among a series of γ-turn mimetic compounds synthesized by a Mitsunobu-reaction-based amination strategy, we identified 1n as a potent and selective LSD1 inhibitor. Compound 1n induced cell cycle arrest and apoptosis through histone methylation in human lung cancer cells. The γ-turn mimetics approach should offer new insights into drug design for LSD1-selective inhibitors.